Evaluation of the Isoniazid Preventive Therapy Care Cascade Among HIV-Positive Female Sex Workers in Mombasa, Kenya. (1st September 2017) - LaCourse, Sylvia M.; Deya, Ruth W.; Graham, Susan M.; Masese, Linnet N.; Jaoko, Walter; Mandaliya, Kischorchandra N.; Overbaugh, Julie; McClelland, R. Scott
Abstract : Background: Kenyan female sex workers (FSWs) have a high HIV prevalence, increasing their tuberculosis (TB) risk. Despite recommendations that HIV-positive individuals be offered isoniazid preventive therapy (IPT), uptake has been limited. Methods: In this longitudinal cohort of HIV-positive FSWs, we retrospectively characterized the IPT care cascade between March 2000 and January 2010, including reasons for cascade loss or appropriate exit. Cascade success required completion of 6 months of IPT. Baseline characteristics were assessed as potential correlates of cascade loss using multivariable logistic regression. Results: Among 642 HIV-positive FSWs eligible for IPT evaluation, median age was 31 years (IQR 26–35) with median CD4 lymphocyte count of 409 (IQR 292–604) cells per cubic millimeter. There were 249 (39%) women who successfully completed 6 months of IPT, 157 (24%) appropriately exited the cascade, and 236 (37%) were cascade losses. Most cascade losses occurred at symptom screen (38%, 90/236), chest radiograph evaluation (28%, 66/236), or during IPT treatment (30%, 71/236). Twenty-nine women were diagnosed with tuberculosis, including one after IPT initiation. Most women initiating IPT completed the course (71%, 249/351); <5% had medication intolerance. Younger women [<25 and 25–35 vs. >35 years; adjusted odds ratio (AOR) 2.65, 95% confidence interval (CI): 1.46 to 4.80 and AOR 1.78, 95% CI: 1.13 to 2.80, respectively], and those evaluated for IPT after antiretroviral availability in 2004 (AOR 1.92, 95% CI: 1.31 to 2.81), were more likely to be cascade losses. Conclusions: Implementation of IPT among HIV-positive FSWs in Kenya is feasible. However, significant losses along the IPT care cascade underscore the need for strategies improving retention in care. Abstract : Supplemental Digital Content is Available in the Text.